Arginine Thiazolidine Carboxylate Stimulates Insulin Secretion through Production of Ca(2+)-Mobilizing Second Messengers NAADP and cADPR in Pancreatic Islets - Park, Dae-Ryoung (PLoS One, 2015)
Oxothiazolidine carboxylic acid is a prodrug of cysteine that acts as an anti-diabetic agent via insulin secretion and the formation of the Ca(2+)-mobilizing second messenger, cyclic ADP-ribose (cADPR). Here we show that a hybrid compound, arginine thiazolidine carboxylate (ATC), increases cytoplasmic Ca(2+) in pancreatic β-cells, and that the ATC-induced Ca(2+) signals result from the sequential formation of two Ca(2+)-mobilizing second messengers: nicotinic acid adenine dinucleotide phosphate (NAADP) and cADPR. Our data demonstrate that ATC has potent insulin-releasing properties, due to the additive action of its two components; thiazolidine carboxylate (TC) and (L)-arginine. TC increases glutathione (GSH) levels, resulting in cAMP production, followed by a cascade pathway of NAADP/nitric oxide (NO)/cGMP/cADPR synthesis. (L)-arginine serves as the substrate for NO synthase (NOS), which results in cADPR synthesis via cGMP formation. Neuronal NOS is specifically activated in pancreatic β-cells upon ATC treatment. These results suggest that ATC is an ideal candidate as an anti-diabetic, capable of modulating the physiological Ca(2+) signalling pathway to stimulate insulin secretion.